CHRONIC NONSPECIFIC LOW BACK PAIN: APPROACH TO CLINICAL DIAGNOSIS. - Dr Sanatan Behera; Prof G S Pattnaik; Dr Chitrita Behera (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: Globally low back pain is a major public health issue affecting all age group. A brutal majority of all cases (80% to 90%) are nonspecific in nature without any recognisable aetiology. Hence delayed diagnosis and inadequate treatment leads to chronic low back pain in many cases affecting productivity and consequent loss of man-hours amongst a sizeable working population. Materials and Methods: 523 cases with low back pain of more than 3 months duration with no specific clinically identifiable cause for back pain were evaluated from August 2019 to July 2021. A detailed history followed by a thorough clinical examination was done for all patients. The clinical criteria for establishing the sub types of chronic non specific low back pain were the predominating symptom and presenting sign. The data were analysed using Microsoft Excel Software. Results: There were 289 males and 234 females with average age being 43.64 years. Discogenic chronic low back pain (CLBP) was the commonest (48.75%) type, and least being sacroiliitis (1.72%). Facetogenic type was seen in older age (57.3 years) group, as against younger age (29.6 years) in postural chronic low back pain. Conclusion: Detail history and meticulous clinical examination is the key to diagnose and differentiate various sub types of nonspecific CLBP. Radiological evaluation, diagnostic blocks and provocative tests may enhance the accuracy in diagnosis.